2010
DOI: 10.1002/jsfa.4228
|View full text |Cite
|
Sign up to set email alerts
|

Higher bioavailability of isoflavones after a single ingestion of aglycone‐rich fermented soybeans compared with glucoside‐rich non‐fermented soybeans in Japanese postmenopausal women

Abstract: The results of this study demonstrated that the isoflavones of aglycone-rich Fsoy were absorbed faster and in greater amounts than those of glucoside-rich Soy in postmenopausal Japanese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 50 publications
6
51
2
Order By: Relevance
“…3e). A number of strategies to increase blood concentration of free isoflavones have been proposed by changing soy food/supplements formula or increasing dosage (15,(42)(43)(44)(45)(46). However, these goals were hard to be realized because of the extensive first-pass metabolism and saturated absorption (16,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…3e). A number of strategies to increase blood concentration of free isoflavones have been proposed by changing soy food/supplements formula or increasing dosage (15,(42)(43)(44)(45)(46). However, these goals were hard to be realized because of the extensive first-pass metabolism and saturated absorption (16,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Izumi et al and Okabe et al reported that soy isoflavone aglycones were absorbed faster and in higher amounts than their glucosides in humans and the bioavailability of the aglycone form of isoflavone was found to be higher than the glycoside form (Izumi et al, 2000;Okabe et al, 2011). Remarkable bioavailability and bioactivity was also reported in foods and medicinal plants containing bioactive aglycone, such as fermented soybeans (Okabe et al, 2011), fermented soymilk ( Kano et al, 2006), and fermented red ginseng . Kuwaki et al found that the antifungal activity of fermented herb formulas against tinea was as high as that of a synthetic fungicide (Kuwaki et al, 2002).…”
Section: Resultsmentioning
confidence: 97%
“…Formononetin (9) was assumed to be produced by the deglycosylation of ononin from the root of P. lobata, and was reported to have vasorelaxation (Wu et al, 2010), antioxidant, and estrogenic effects (Mu et al, 2009). Izumi et al and Okabe et al reported that soy isoflavone aglycones were absorbed faster and in higher amounts than their glucosides in humans and the bioavailability of the aglycone form of isoflavone was found to be higher than the glycoside form (Izumi et al, 2000;Okabe et al, 2011). Remarkable bioavailability and bioactivity was also reported in foods and medicinal plants containing bioactive aglycone, such as fermented soybeans (Okabe et al, 2011), fermented soymilk ( Kano et al, 2006), and fermented red ginseng .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermented traditional medicine (FTM) has garnered attention for its enhanced biological activity compared to traditional medicine (Wei et al, 2007;Okabe et al, 2011). Several studies using single herbs and fungi support the availability and efficacy of FTM.…”
Section: Introductionmentioning
confidence: 99%